University Students’ Knowledge about Welfare Technologies within Active Aging Concept: An Online Survey Interview - Tímea S. Zaťková; Jana Šolcová; Ľubica Jamborová; Miroslava Tokovská (Ital Publication, 2024)
Welfare technology has made a significant impact on society, supporting people´s communication, independence, and day-to-day living. This study aims to investigate university students' knowledge of welfare technologies related to smart active aging. The research was guided by the following questions: 1: What do Slovak university students know about welfare technologies? 2: How are welfare technologies used in the households of university students and their relatives? An online interview survey with reflexive thematic analysis was conducted with 120 university students at two universities in Slovakia. Findings show four themes that were identified: (1) Different interpretations of welfare technologies. (2) Broadening students’ knowledge about welfare smart technologies. (3) Attitudes towards smart and welfare technologies. (4) Gap in practical usage of welfare technologies. Welfare technology is a new topic connected to active aging. Primarily, the younger generation, as proved, has low knowledge on this theme. The novelty of the study lies in connecting the welfare technology concept with the education of the younger generation. Welfare technologies have the potential to promote positive intergenerational relationships, autonomy, and mental and physical well-being among older adults. As for improvements, smart active aging and welfare technology concepts should be incorporated more intensively into higher education. This would help curb the knowledge gap and ensure the development of skills for implementing welfare technologies in the daily lives of their elderly relatives. Doi: 10.28991/ESJ-2024-08-03-017 Full Text: PDF